Public R&D support, innovation, and spillovers: A dynamic spatial panel approach to firms - Bongsuk Sung; Dan Zhang; Sang-Do Park (Heliyon)
From the perspective of a heterogeneous firm framework, we investigate the direct and spillover effects of public research and development (R&D) subsidies, firm heterogeneity, and external factors on innovation. Our analysis is based on panel data from manufacturing firms in Korea. We find three apparent roles of public R&D subsidy in enhancing firm-level innovation. First, public R&D subsidy has a direct positive impact on innovation in both the short and long run. Second, it does not have a stand-alone spillover effect on innovation. Third, public R&D subsidies have a positive spillover effect on innovation when combined with organizational slack in the short and long run and with leverage and firm size in the short run. Moreover, our analysis reveals that the impact of public subsidies, firm heterogeneity, external factors, and their interaction with innovation is primarily observed in firms with high absorptive capacity, not in those with low absorptive capacity. Based on these findings, the study recommends that when a government formulates its R&D policies, in order to enhance the efficiency and effectiveness of public R&D subsidies, it is necessary to prioritize understanding the various conditions and circumstances associated with the public R&D-productivity nexus. It is especially crucial to keep in mind that when firm heterogeneity—as a source of absorptive capacity and organizational learning—and the similarity of technology-based innovations are properly considered, public R&D subsidies can be efficient and effective policy tools for increasing direct benefits and inter-firm spillovers.